Design of Vegetable Bada Promotional Media Using Still Life Photography Techniques - Delita Rahmanda Sari; Rina Nurfitri; Yekti Asmoro Kanthi; Ahmad Zakiy Ramadhan (LPPM STIKI Malang, 2022)
The design of Bada's Vegetable Promotional Media Using Still Life Photography Techniques was created to assist Bada in solving problems in terms of promotional media (building new media for resellers) and Bada's visual assets so as to produce Promotional Media in the form of Product Catalogs, Instagram Feeds and Bada Instagram Stories, Posters, Brochures, X-Banners, and Photo-based Calendar Authentic Bada vegetables relevant and friendly with pre-owned sales platform. Product photos of Bada vegetables applying the Still Life Photography technique which is the main element in the promotional media that is designed. As for this research, testing has been carried out on the results of the design through a questionnaire to 20respondents (customers of Bada)